Novel electrically conductive polyurethane/montmorillonite-polypyrrole nanocomposites - S. D. A. S. Ramoa; G. M. O. Barra; C. Merlini; S. Livi; B. G. Soares; A. Pegoretti (eXPRESS Polymer Letters)
This work describes the production of electrically conductive nanocomposites based on thermoplastic polyurethane (TPU) filled with montmorillonite-dodecylbenzenesulfonic acid-doped polypyrrole (Mt-PPy.DBSA) prepared by melt blending in an internal mixer. The electrical conductivity, morphology as well as the rheological properties of TPU/Mt-PPy.DBSA nanocomposites were evaluated and compared with those of TPU nanocomposites containing different conductive fillers, such as polypyrrole doped with hydrochloride acid (PPy.Cl) or dodecylbenzenesulfonic acid (PPy.DBSA) or montmorillonite-hydrochloride acid-doped polypyrrole (Mt-PPy.Cl), prepared with the same procedure. The TPU/Mt-PPy.DBSA nanocomposites display a very sharp insulator-conductor transition and the electrical percolation threshold was about 10 wt% of Mt-PPy.DBSA, which was significantly lower than those found for TPU/Mt-PPy.Cl, TPU/PPy.Cl and TPU/PPy.DBSA. Morphological analysis highlights that Mt-PPy.DBSA filler was better distributed and dispersed in the TPU matrix, forming a denser conductive network when compared to Mt-PPy.Cl, PPy.Cl and PPy.DBSA fillers. This morphology can be attributed to the higher site-specific interaction between TPU matrix and Mt-PPy.DBSA. The present study demonstrated the potential use of Mt-PPy.DBSA as new promising conductive nanofiller to produce highly conductive polymer nanocomposites with functional properties.